Measurement of methylamines in seawater using solid phase microextraction and gas chromatography. (12th July 2018) - Cree, Charlotte H. L.; Airs, Ruth; Archer, Stephen D.; Fitzsimons, Mark F.
Abstract: The methylamines form part of the marine organic nitrogen pool. Although they are ubiquitous in marine systems, little is known about their distribution, production, and fate in the marine environment. Analytical methods have been developed for their analysis in marine waters, but these have employed custom‐made apparatus, limiting data to a few studies. Here, we report a method developed for the determination of methylamines in seawater which combines headspace solid phase microextraction (SPME) and gas chromatography with selective nitrogen detection. Gaseous methylamines were pre‐concentrated from water samples (∼ 1 L) heated to 60 °C, onto a polydimethylsiloxane/divinylbenzene SPME fiber located in the headspace of the extraction flask. The analytes were then thermally desorbed from the fiber in a gas chromatograph containing a CP‐Volamine column and a nitrogen–phosphorus detector. The method was routinely calibrated down to 1 nM for all three analytes using matrix‐matched external standards. Limits of detection were determined operationally and ranged from 0.4 nM to 2.9 nM during two sampling campaigns. The analytes were detected in seawater samples from the English Channel and Southern Ocean where concentrations up to 20 nM and 5.6 nM were measured, respectively, consistent with previously reported levels. We propose this method for the analysis of methylamines, and other low‐molecular weight amines, as it is sensitive, robust, and the necessary equipment is widely available.